Learning manager for remote experimentation with optoelectronic devices (2015)
Both the Internet and communications and information technology (ICT), are making a valuable contribution to education. Remote experimentation is an example of the contribution that becomes as a solution to various problems involved with practices in situ, which are a fundamental aspect in the development of skills in engineering education. In this work, we have implemented a learning manager to experience with optoelectronic devices via internet, this tool is composed of a hardware platform comprising a set of electronic components such as light emitting diodes and optocouplers, each one with its respective signal conditioning and communication interfaces; additionally, a Web 2.0 user interface and learning management concepts and content are included. Those facilitate administration and promoting collaborative learning regarding social networks.